Synthesis of fluoranthenes by hydroarylation of alkynes catalyzed by gold(I) or gallium trichloride - Pascual, Sergio; Bour, Christophe; de Mendoza, Paula; Echavarren, Antonio M. (Beilstein Journal of Organic Chemistry, 2011)
Electrophilic gold(I) catalyst 6 competes with GaCl3 as the catalyst of choice in the synthesis of fluoranthenes by intramolecular hydroarylation of alkynes. The potential of this catalyst for the preparation of polyarenes is illustrated by a synthesis of two functionalized decacyclenes in a one-pot transformation in which three C–C bonds are formed with high efficiency.
Keywords: alkynes; gold(I) catalysis; hydroarylation; polyarenes